Evaluasi Capaian Kinerja Tahun 2020 Dalam Penerapan WFH (Work From Home) Di Masa Pandemi Covid-19 - Emil Kristanti (Universitas Kuningan, 2022)
ABSTRACTThis study aims to determine the evaluation of performance achievements from research activities at the Informatics Research Center-LIPI in 2020 as a result of the implementation of the WFH (work from home) work system and with a decrease in performance targets as a result of the budget refocusing policy during the covid-19 pandemic. The method used by the author is a qualitative description approach by identifying performance achievements in 2020 in the application of WFH during the covid-19 pandemic at the Informatics Research Center-LIPI from related sources and supported by supporting data from journals, articles, and other literature. The result showed that the implementation of the WFH work system at the Informatics Research Center-LIPI in 2020 during the covid-19 did not reduce performance achievement, but instead increased performance achievement. WFH work system as a new culture during the pandemic does not reduce employee motivation to keep performing. WFH as a part of the Flexible Working Arrangements (FWA) concept can be an opportunity in the future to be implemented either during or post-pandemic while prioritizing productivity, maintaining performance, or even increasing toward e-government by strengthening digital transformation.Keywords: Evaluation; Performance Achievement; WFH; Pandemic. ABSTRAKPenelitian ini bertujuan untuk mengetahui evaluasi capaian kinerja dari kegiatan penelitian di Pusat Penelitian Informatika-LIPI tahun 2020 sebagai dampak penerapan sistem kerja WFH (Work From Home) dan dengan penurunan target kinerja sebagai dampak kebijakan refocusing anggaran selama masa pandemi covid-19. Metode yang digunakan penulis adalah dengan pendekatan deskripsi kualitatif dengan mengidentifikasi capaian kinerja tahun 2020 dalam penerapan WFH selama pandemi covid-19 di Pusat Penelitian Informatika-LIPI dari sumber terkait dan didukung dengan data pendukung baik dari jurnal, artikel maupun literatur lainnya. Hasil penelitian menunjukkan bahwa penerapan sistem kerja WFH di Pusat Penelitian Informatika-LIPI pada tahun 2020 selama masa pandemi covid-19 tidak menurunkan capaian kinerja, tetapi justru capaian kinerja meningkat. Sistem kerja WFH sebagai budaya baru di masa pandemi tidak mengurangi motivasi pegawai untuk tetap berkinerja. WFH sebagai bagian dari konsep Flexible Working Arrangement (FWA) bisa menjadi peluang ke depannya untuk dilaksanakan baik di masa atau pasca pandemi dengan tetap mengedepankan produktifitas capaian kinerja tetap terjaga atau bahkan meningkat menuju e-government dengan penguatan transformasi digital.Kata Kunci: Evaluasi; Capaian Kinerja; WFH; Pandemi.